Biodetection of misfolded insulin based on plasmonic nanocavity - Zhang, Xinyi (Nanyang Technological University, 2022)
Due to the increasing demands in healthcare, the detection of early stage of chronic diseases and the treatment has attracted significant interest nowadays. Since the changes in indicators, such as the transformation in biomolecular structure and physical/chemical properties of biomolecules, conventional technologies remain challenging to identify or detect such changes at an earlier stage. In this dissertation, our aim is to propose a novel sensing platform which can be used to identify subtle structural changes of chronic proteins at different stages. Herein structure which consists of glass substrate, DBR mirror and silver nanocube is designed to detect fluorescent dyed misfolded insulin's optical properties. Two types of fluorescent dyes were used in this project, including Rhodamine 6G and ThT. By comparing the experimental and simulated results under different incubation time, the corresponding amyloid diameter to different insulin growing time can be determined through the relative resonant intensity. The function of the proposed structure reveals that it has the potential to be applied in the biosensing and detection of some protein-misfolding diseases.